Rennäringen inför milleniumsskiftet 2000 - Idivuoma, Per Gustav (Rangifer, 1999)
Reindeer owner and chairman of SSR Per Gustav Idivuoma summarizez the challenges of Swedish reindeer husbandry. The lecture was held in Swedish.